Today's Business Communication: A How-to Guide for the Modern Professional - Snyder, Jason L.; Forbus, Robert (Business Expert Press, 2014)
This handy guide to excellent business communications is perfect for both college students and business professionals. Whether preparing for a career, launching a career, or advancing in a career, the savvy professional understands that every organization expects employees to be exceptional business communicators. Today's Business Communication: A How-to Guide for the Modern Professional leads readers through the most frequently encountered business communication situations. Two business partners who are also business school professors share their combined 30 years of marketing and communication experience with readers in this accessible, entertaining, and informative guide. The authors enhance the readers' experience through anecdotes from business professionals from different industries.
Keywords: Business communication; dept.mkt; faculty_collection

Industry Applications of Market Sensing Foreword to the Special Issue of Journal of Marketing and Management - Prince, Melvin; Priporas, Constantinos-Vasilios (Journal of Marketing and Management, 2014)
Num Pages: 5 Place: Beverly Hills, United States
Keywords: Business And Economics–Management; Business And Economics–Marketing And Purchasing; Competition; Competitive advantage; Consumers; Knowledge management; Marketing; Product development; Product lines; Research; SWOT analysis; dept.mkt; ⛔ No DOI found

The effects of part-time MBA programs on students: the relationships between students and their employers - Prince, Melvin; Burns, David J; Manolis, Chris (The Journal of Education for Business, 2014)
The authors explore how the relationship between part-time master of business administration (MBA) students and their employers changes as students proceed through their MBA program by examining the degree to which students are integrated into their employer organizations. Significant positive relationships observed between students’ progress through their MBA program and the integration factors of coworker support and future prospects with their employers suggest that an MBA education can have a positive effect on employee–employer integration levels. Consequently, in addition to increasing business knowledge and skills, an MBA degree appears to assist with integrating employees and employers. © 2014, Copyright © Taylor & Francis Group, LLC.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-299-392-333-109 tex.type: [object Object]
Keywords: MBA education; coworker support; dept.mkt; graduate education; part-time MBA students; training